Case report: Primary cardiac lymphoma manifesting as superior vena cava syndrome - Kassab, Joseph; Gebrael, Georges; Chedid El Helou, Michel; El Dahdah, Joseph; Haroun, Elio; Kassab, Rebecca; Abou Ali, Saad; Khabbaz, Ziad; Kassab, Roland (Frontiers in Cardiovascular Medicine, 2023)
A 64-year-old man presented with symptoms indicative of superior vena cava syndrome. Imaging work-up revealed an obstructing right atrial mass, which was subsequently excised and diagnosed as primary cardiac lymphoma. Post-surgery, the patient showed significant clinical improvement and was started on a chemotherapy regimen with complete remission at 1 year.